Maritime Jurisdiction Disputes in Turkey-Greece Relations - Fuat Aksu (Avrasya İncelemeleri Dergisi)
Since 1923, 14 of Turkey's foreign policy crises have occurred directly or indirectly with Greece. Although the crises were prevented before turning into an allout war between the parties, reaching a permanent solution to the disputes was impossible. The disputes between Turkey and Greece are related but also have different characteristics. Many factors make it difficult to resolve these disputes through peaceful resolution methods. The uniqueness of geography, the emergence of technological innovations that require redefining the sovereign rights of states, and the disruption of the delicate balance established by statusestablishing agreements with actual violations are some of these. In addition to these, the negativities created by the historical legacy, negative perceptionsregarding identity and intention, the instrumentalization of disputes in domestic and foreign policy and the influence of third actors should not be ignored. In addition, the positive and negative guiding effects of the leaders in the two countries and the actors who have the potential to influence public opinion can also be mentioned. This study will focus on the contractual law dimension of the disputes regarding maritime jurisdictions between the parties, how they interpret the concepts of sovereignty and sovereign rights, and their attempts to change the status quo with fait accompli. The sovereignty of the islands surrounding Anatolia, the problems encountered in determining their jurisdictions, and the differences of opinion that make the solution to these problems difficult will be discussed.